Inovasi dan Kemasan Produk UMKM dengan Memanfaatkan Ekosistem Digital untuk Meningkatkan Sales di Kota Sukabumi - Djaddang, Syahril; Nawasiah, Nana; Wijaya, Agustinus Miranda; Syam, M. Ardiansyah; Sari, Lola Fitria; Riskarini, Dian (Jurnal Nusantara Mengabdi, 2024)
Purpose: Community Service aims to train and assist in the digital marketing Android-based MSME products after the COVID-19 pandemic. Methodology: The PkM method used was FGD, interviews, and random sampling from MSMEs in Sukabumi. Assistance with the digitalization of MSME products, and as a basis for implementing Android-based digital marketing for MSME products with marketing applications in marketplaces, such as; Lasada, Shoopee, and IG to increase sales for MSMEs in the city of Sukabumi Results: The results of this PkM are expected to be used to develop digital marketing for Android-based MSME products. PkM is important for creating the digitalization of MSME products and building society's entrepreneurial spirit. Limitations: By utilizing the digital ecosystem, MSMEs in Sukabumi City can overcome several existing limitations and open up opportunities to increase sales in local and wider markets. Contribution: The Pancasila University Jakarta Postgraduate School Abdimas Team together with Muhammadiyah University Sukabumi (UMMI) and Sukabumi MSMEs carried out community service with the theme "The Benefits of Marketing Digitalization for Android-Based MSME Products, such as; Moci, Krupuk, and typical Sukabumi culinary delights, to encourage increased sales." The event which was held offline was held at the Audit Lab of the UMMI Faculty of Economics in Sukabumi City, Friday (16/6/2023).